Multi-antigen-targeted T-cell therapy to treat patients with relapsed/refractory breast cancer - Valentina Hoyos; Spyridoula Vasileiou; Manik Kuvalekar; Ayumi Watanabe; Ifigeneia Tzannou; Yovana Velazquez; Matthew French-Kim; Wingchi Leung; Suhasini Lulla; Catherine Robertson; Claudette Foreman; Tao Wang; et al. (Therapeutic Advances in Medical Oncology, 2022)
Purpose: Adoptively transferred, ex vivo expanded multi-antigen-targeted T cells (multiTAA-T) represent a new, potentially effective, and nontoxic therapeutic approach for patients with breast cancer (BC). In this first-in-human trial, we investigated the safety and clinical effects of administering multiTAA T cells targeting the tumor-expressed antigens, Survivin, NY-ESO-1, MAGE-A4, SSX2, and PRAME, to patients with relapsed/refractory/metastatic BC. Materials and methods: MultiTAA T-cell products were generated from the peripheral blood of heavily pre-treated patients with metastatic or locally recurrent unresectable BC of all subtypes and infused at a fixed dose level of 2 × 10 7 /m 2 . Patients received two infusions of cells 4 weeks apart and safety and clinical activity were determined. Cells were administered in an outpatient setting and without prior lymphodepleting chemotherapy. Results: All patients had estrogen receptor/progesterone receptor positive BC, with one patient also having human epidermal growth factor receptor 2-positive. There were no treatment-related toxicities and the infusions were well tolerated. Of the 10 heavily pre-treated patients enrolled and infused with multiTAA T cells, nine had disease progression while one patient with 10 lines of prior therapies experienced prolonged (5 months) disease stabilization that was associated with the in vivo expansion and persistence of T cells directed against the targeted antigens. Furthermore, antigen spreading and the endogenous activation of T cells directed against a spectrum of non-targeted tumor antigens were observed in 7/10 patients post-multiTAA infusion. Conclusion: MultiTAA T cells were well tolerated and induced disease stabilization in a patient with refractory BC. This was associated with in vivo T-cell expansion, persistence, and antigen spreading. Future directions of this approach may include additional strategies to enhance the therapeutic benefit of multiTAA T cells in patients with BC.